ANALYTICAL STUDY OF THE ROLE OF THE HEAD OF STATE ACCORDING TO THE (2005) CONSTITUTION OF THE REPUBLIC OF IRAQ (American Journal of Research in Humanities and Social Sciences, 2025)
According to the 2005 Iraqi Constitution, the President of the Republic plays a highly important and complex role, given his active and influential role in achieving political stability within the system of government, a role theoretically supported by the constitutional document, In practical terms, its role is demonstrated through the political agreements that occur between political blocs and parties, which are both important and challenging Due to what is happening on the political scene following the parliamentary elections for the House of Representatives, especially what occurred after the last elections in 2021, which effectively obstructed the election of the President of the Republic, this stands as an obstacle to achieving the desired stability